2023
DOI: 10.1186/s40634-023-00688-8
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality simulation training improve diagnostic knee arthroscopy and meniscectomy skills: a prospective transfer validity study

Alexandre Tronchot,
Tiphaine Casy,
Nicolas Vallee
et al.

Abstract: Purpose Limited data exist on the actual transfer of skills learned using a virtual reality (VR) simulator for arthroscopy training because studies mainly focused on VR performance improvement and not on transfer to real word (transfer validity). The purpose of this single-blinded, controlled trial was to objectively investigate transfer validity in the context of initial knee arthroscopy training. Methods For this study, 36 junior resident orthopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…A study published by Tronchot et al showed that skills developed on a hybrid VR simulator could be successfully transferred to bench-top and cadaveric models [103]. This suggests that training with a VR arthroscopy surgical simulator has the potential to safely improve arthroscopic skills in the operating room.…”
Section: Education and Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…A study published by Tronchot et al showed that skills developed on a hybrid VR simulator could be successfully transferred to bench-top and cadaveric models [103]. This suggests that training with a VR arthroscopy surgical simulator has the potential to safely improve arthroscopic skills in the operating room.…”
Section: Education and Trainingmentioning
confidence: 99%
“…It is currently recognized that VR simulators may play a critical role in the evolution of surgical training, with the ultimate goal of enhancing the quality of patient care [103][104][105]. With surgical and educational applications, an algorithm has been developed that automatically segments the arthroscopic frame to offer surgeons added contextual awareness.…”
Section: Education and Trainingmentioning
confidence: 99%